2016
DOI: 10.1038/srep21343
|View full text |Cite
|
Sign up to set email alerts
|

Dried plum diet protects from bone loss caused by ionizing radiation

Abstract: Bone loss caused by ionizing radiation is a potential health concern for radiotherapy patients, radiation workers and astronauts. In animal studies, exposure to ionizing radiation increases oxidative damage in skeletal tissues, and results in an imbalance in bone remodeling initiated by increased bone-resorbing osteoclasts. Therefore, we evaluated various candidate interventions with antioxidant or anti-inflammatory activities (antioxidant cocktail, dihydrolipoic acid, ibuprofen, dried plum) both for their abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 64 publications
(119 reference statements)
3
41
0
1
Order By: Relevance
“…Among the parameters analyzed, IR only induced changes in Tb.Th and Tb.Sp. Unlike reports by others, there were no significant changes in Tb.N from any of the treatment groups relative to the sham-irradiated control group 21,43,44 . When HU was combined with IR, Tb.Th decreased by 9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the parameters analyzed, IR only induced changes in Tb.Th and Tb.Sp. Unlike reports by others, there were no significant changes in Tb.N from any of the treatment groups relative to the sham-irradiated control group 21,43,44 . When HU was combined with IR, Tb.Th decreased by 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has reported that mice fed a diet composed of Dried Plum (DP) prevented cancellous bone loss caused by ionizing radiation (IR), both low-LET such as gamma ( 137 Cs) and a mixture of both low-LET and high-LET (sequential beam of proton, 1 H and iron, 56 Fe). The proposed mechanism for DP's protective effect is via the prevention of radiation-induced increases in markers of bone resorption, inflammation and oxidative stress 43 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After title/abstract review, 22 articles were screened in full-text and included in this comprehensive review [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,31,32]. Two additional studies [30,33] were included after examination of the reference lists of the 22 studies identified in the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…However, 3 days after lethal-dose gamma irradiation, metabolite levels in urine samples of nonhuman primates had some outliers compared to controls, indicating significant biological variations (21). Furthermore, mouse tissues were able to recover at day 11 after 2.0 Gy gamma irradiation (22). The goal of this study was to investigate changes in metabolites of liver tissue at time points close to days 3 and 11 postirradiation; ultimately, days 4 and 11 postirradiation were selected Six groups of animals were exposed to gamma radiation (n = 27; Supplementary Table S1; http://dx.doi.org/10.1667/RR14602.1.S1) [0 Gy (n = 4), 3.0 Gy (n = 10; 2 groups) and 7.8 Gy (n = 4)] or proton radiation [0 Gy (n = 4) or 3.0 Gy (n = 5)], respectively.…”
Section: Methodsmentioning
confidence: 99%